Depression in primary care: three key challenges. Issue 996 (18th November 2008) - Lester, H; Howe, A
Abstract : The recognition and treatment of depression is a challenging area of clinical practice, especially in primary care where there are many patients with various presentations and a multitude of causes for distress. The prevalence of depression is increasing, and it is predicted to become second only to ischaemic heart disease as a cause of morbidity worldwide. Fortunately, the research evidence on effective approaches is increasing. This article looks at how we can best identify, treat and understand the perspectives of people with depression who are seen in primary care. Simple questionnaires can provide effective screening in generalist settings, particularly when targeting high-risk groups such as those with cardiovascular comorbidity or recurrent unexplained symptoms. Guidelines now exist for use of antidepressants and cognitive behavioural therapy for mild to moderate depression, although the latter needs effective policy implementation in clinical practice to maximise its impact for patients. However, there is also consistent evidence from service users that people with depression want individualised care which takes into account their preferences and concerns, even if this entails departure from guidelines. Adherence to treatment is low in many studies, and remodelling of services can easily lead to gaps in consistent approaches to personal care. The research challenges for the future include clarification of which patient groups merit proactive screening, how to enhance adherence, and the relative merits and outcomes of pharmacological versus behavioural therapies. Changes in policy and service configuration can improve or destabilise effective care, but high-quality and flexible intervention with patients with mild to moderate depression is likely to be cost-effective in view of the high prevalence and disease burden of this distressing problem.